2020
DOI: 10.1016/s2214-109x(20)30343-0
|View full text |Cite
|
Sign up to set email alerts
|

Adverse health effects associated with household air pollution: a systematic review, meta-analysis, and burden estimation study

Abstract: Background 3 billion people worldwide rely on polluting fuels and technologies for domestic cooking and heating. We estimate the global, regional, and national health burden associated with exposure to household air pollution.Methods For the systematic review and meta-analysis, we systematically searched four databases for studies published from database inception to April 2, 2020, that evaluated the risk of adverse cardiorespiratory, paediatric, and maternal outcomes from exposure to household air pollution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
182
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(185 citation statements)
references
References 35 publications
(67 reference statements)
2
182
1
Order By: Relevance
“…Poverty has also been suggested to be a key factor in preventing access to clean fuel but also compounds the burden associated with HAP by worsening access to adequate health care [ 51 ]. This may be a contributing factor to the regional disparity seen between the mostly lower socio-economic demographic of the North compared to the mostly higher socio-economic demographic of the South.…”
Section: Discussionmentioning
confidence: 99%
“…Poverty has also been suggested to be a key factor in preventing access to clean fuel but also compounds the burden associated with HAP by worsening access to adequate health care [ 51 ]. This may be a contributing factor to the regional disparity seen between the mostly lower socio-economic demographic of the North compared to the mostly higher socio-economic demographic of the South.…”
Section: Discussionmentioning
confidence: 99%
“…Figures 3-5 present the incremental cost pre-and post-intervention with varying levels of effectiveness and intervention costs for people with asthma, living in extreme risk dwellings that are considered either non-decent, to have a usable floor area <90 m 2 or to have any damp problems respectively. The results of the analyses demonstrate that at a given level of effectiveness, the threshold for the upfront cost of the intervention to remain cost-saving is equivalent across the different home characteristics.…”
Section: Two-way Sensitivity Analysismentioning
confidence: 99%
“…People in Europe spend up to 90% of their lives indoors and 66% of this time is spent at home [ 1 ]. Indoor air quality has an impact on multiple health outcomes, including respiratory and cardiovascular illness, allergic symptoms, cancers and premature mortality [ 2 , 3 ]. Common pollutants include particulate matter (PM 2.5 and PM 10 ); nitrogen dioxide (NO 2 ); and volatile organic compounds (VOCs) including benzene, formaldehyde and polycyclic aromatic hydrocarbons (PAHs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Studies have shown that emissions from kerosene combustion increase the risk of asthma, pulmonary tuberculosis, cardiovascular disease, cerebrovascular disease, cancer, stillbirth, etc. 10 Plant-based remedies have proven to be useful in the treatment and management of diseases and specifically the toxicity caused by hydrocarbons and other constituents of petroleum and petrochemical products. 11 It is estimated that up to 80% of the population in developing countries rely on traditional medicine for their primary healthcare need.…”
mentioning
confidence: 99%